Does social media use at work lower productivity?. (15th January 2020) - Vithayathil, Joseph; Dadgar, Majid; Osiri, J. Kalu
We conducted an empirical study that analysed the relationship between the use of social media at work and project success at work. This study adds to the emerging literature on the impact of social media use on organisational outcomes. We found that only one of the four popular social media platforms studied adds value to the workplace. Specifically, we found the use of Facebook at work, whether controlling for age, gender and education or not, to be negatively associated with project success. The use of LinkedIn (with the controls) and the use of other social media (without the controls) were both found to be positively associated with work project success. Other social media was used to capture all other social media platforms, including firm-specific or work-specific social media platforms. We explained our results using social network analysis (SNA), the strength of weak ties and information diffusion theories. Our findings have implications for practice, policy and future research.